Response of Two Varieties of Cucumber (Cucumis sativus L.) to Silicon and Chlorine Applied in Shade Houses - Cázarez-Flores, Luz Llarely; Partida-Ruvalcaba, Leopoldo; Velázquez-Alcaraz, Teresa de Jesús; Zazueta-Torres, Norma Delia; Yáñez-Juárez, Moisés Gilberto; Angulo-Castro, Azareel; Díaz-Valdés, Tomás (REVISTA TERRA LATINOAMERICANA, 2024)
Plant growth, higher yield and fruit quality are positive ef fects due to the absorption of silicon (Si) and chlorine (Cl), which contributes to mitigating stress due to biotic or abiotic factors and recovering plant growth. The objective of this research was to know what the ef fect of Si or Cl does on morphometric variables, production quality and yield of the cucumber crop. A complete randomized block design was applied, four repetitions and ten treatments in seedlings: six doses of 20, 30 and 50 mg L-1 of Si or Cl, three doses with the volume:volume (v:v) ratio of 20 :20, 30:30 and 50:50 mg L-1 Si:Cl, plus the control. In plants transplanted in soil, already with five true leaves, there were nine treatments: six doses of 20, 30 and 50 mg L-1 of Si or Cl, two with the v:v ratio of 20:20 and 30:30 mg L-1 Si:Cl, and the witness. In pickle cucumber seedlings, the high dose of Cl was more ef fective in increasing leaf greenness and stem length; leaf size was greater in seedlings with the high dose of Si; while low doses of Cl or Si caused greater dry weight of roots. In the ˈModanˈ cultivar, the greenness did not change, the stem length was greater with the intermediate dose of Si, while the size of leaves was better expressed in plants with the lowest dose of Si. So perhaps the greater number of roots, the chlorophyll content and the leaf area influenced the higher yield to be expressed where Si or Cl was fertilized, as well as the firmness, TSS and °Brix of the fruits to improve.